2003
DOI: 10.1046/j.1440-1703.2003.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat differentiation of Lauraceae species in a tropical lower montane forest in northern Thailand

Abstract: Dependency on topographical habitat was examined for Lauraceae tree species in a lower montane forest using a large‐scale research plot established at Doi Inthanon National Park, northern Thailand. Twenty species of 10 genera of Lauraceae were recorded in a 7.5‐ha part of the plot; Lauraceae accounted for 18% of the total basal area. Lauraceae was the most species‐rich and most abundant family in the plot. In a cluster analysis based on the matrix of spatial associations between species, two clusters were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 27 publications
6
47
0
1
Order By: Relevance
“…In the plots, the dominant woody species therefore coexist and are strongly associated with various habitats that require for survival and recruitment. Some studies have revealed the importance of topographical variations in determining the species coexistence (Sri-ngernyuang et al 2003;Yamada et al 2006). Our study results showed that the soil variations in the desert and oasis transition belt determine the co-occurrence of woody species after sandy desertification.…”
Section: Spatial Associations and Competition Of Desert Woody Speciessupporting
confidence: 52%
“…In the plots, the dominant woody species therefore coexist and are strongly associated with various habitats that require for survival and recruitment. Some studies have revealed the importance of topographical variations in determining the species coexistence (Sri-ngernyuang et al 2003;Yamada et al 2006). Our study results showed that the soil variations in the desert and oasis transition belt determine the co-occurrence of woody species after sandy desertification.…”
Section: Spatial Associations and Competition Of Desert Woody Speciessupporting
confidence: 52%
“…The montane forest is typically moist and cool. However, the plant diversity and the hydrological cycles in these forests vary with altitude and topographical habitat (Sri-ngernyuang et al 2003;Khamyong et al 2004;Withawatchutikul et al 2011). The soil in this forest was deep, classified in Order Ultisols, and contained the high content of organic matter as well as the low bulk density in surface soil with some organic layers on the forest floor (Pornleesangsuwan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some environmental variables, particularly soil texture, cation composition and topography, are repeatedly reported as important in determining tropical forest composition (Costa et al 2005;Sri-Ngernyuang et al 2003;Tuomisto et al 2002;Valencia et al 2004;Vormisto et al 2004). The availability of complete floristic and soil data sets that are needed to address these questions is very limited given the vast extent of the tropics.…”
Section: Introductionmentioning
confidence: 99%